Maryam's magic : the story of mathematician Maryam Mirzakhani - Reid, Megan (Balzer + Bray, 2021)
The true story of Maryam Mirzakhani, an Iranian girl whose creativity and love of stories helped her and the world see math in a new way, and who was the only woman ever to win the Fields Medal, the most prestigious honor in mathematics.